Interactions Between Alcohol Metabolism Genes and Religious Involvement in Association With Maximum Drinks and Alcohol Dependence Symptoms - Chartier, Karen G. (J Stud Alcohol Drugs, 2016)
OBJECTIVE: Variations in the genes encoding alcohol dehydrogenase (ADH) enzymes are associated with both alcohol consumption and dependence in multiple populations. Additionally, some environmental factors have been recognized as modifiers of these relationships. This study examined the modifying effect of religious involvement on relationships between ADH gene variants and alcohol consumption–related phenotypes. METHOD: Subjects were African American, European American, and Hispanic American adults with lifetime exposure to alcohol (N = 7,716; 53% female) from the Collaborative Study on the Genetics of Alcoholism. Genetic markers included ADH1B-rs1229984, ADH1B-rs2066702, ADH1C-rs698, ADH4-rs1042364, and ADH4-rs1800759. Phenotypes were maximum drinks consumed in a 24-hour period and total number of alcohol dependence symptoms according to the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition. Religious involvement was defined by self-reported religious services attendance. RESULTS: Both religious involvement and ADH1B-rs1229984 were negatively associated with the number of maximum drinks consumed and the number of lifetime alcohol dependence symptoms endorsed. The interactions of religious involvement with ADH1B-rs2066702, ADH1C-rs698, and ADH4-rs1042364 were significantly associated with maximum drinks and alcohol dependence symptoms. Risk variants had weaker associations with maximum drinks and alcohol dependence symptoms as a function of increasing religious involvement. CONCLUSIONS: This study provided initial evidence of a modifying effect for religious involvement on relationships between ADH variants and maximum drinks and alcohol dependence symptoms.